2012
DOI: 10.1089/pop.2011.0089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship Between Individual Well-Being and Future Health Care Utilization and Cost

Abstract: Escalating health care expenditures highlight the need to identify modifiable predictors of short-term utilization and cost. Thus, the predictive value of individual well-being scores was explored with respect to 1-year health care expenditures and hospital utilization among 2245 employees and members of a health plan who completed the Well-Being Assessment (WBA). The relationship between well-being scores and hospital admissions, emergency room (ER) visits, and medical and prescription expenditures 12-months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…First, the significant relationships between overall well-being and follow-up health care costs and utilization confirm previous work that found well-being as a leading indicator of health care outcomes. 12 This finding is particularly noteworthy given the high amount of variance in the distribution of claims …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, the significant relationships between overall well-being and follow-up health care costs and utilization confirm previous work that found well-being as a leading indicator of health care outcomes. 12 This finding is particularly noteworthy given the high amount of variance in the distribution of claims …”
Section: Discussionmentioning
confidence: 97%
“…Health care outcomes such as medical and pharmacy costs and hospital utilization have been linked to overall well-being in prior studies. 12,13 Although much of the prior literature on health care outcomes has focused on the physical health and behavioral risk subdomains of overall well-being, 14,15 other well-being subdomains related to work, social relationships, finances, and one's community are associated with chronic and acute illness. [16][17][18][19] Only 1 study has investigated the relationship between overall well-being and health care outcomes longitudinally, finding well-being to be a significant predictor of future health care costs and utilization, controlling for past outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A study published recently demonstrated a positive relationship between an improvement in an employee's feeling of well-being and the effect on health care utilization and costs. 4 Harrison and colleagues found that a statistically significant (p < 0.01) inverse relationship exists between self-reported well-being scores and short-term health care utilization and spending. Employee members of a health care plan (n=2245) were asked to complete a questionnaire that measured well-being on a 100 point scale.…”
Section: Discussionmentioning
confidence: 99%
“…Employee members of a health care plan (n=2245) were asked to complete a questionnaire that measured well-being on a 100 point scale. 4 When analyzing the health care utilization and spending of these individuals over a 12 month time period, their results showed that for every one point increase on the well-being scale, a 2.2% decrease in hospital admissions was demonstrated. 4 Additionally, every one point increase correlated to a 1.7% decrease in emergency room visits, and respondents were 1.0% less likely to incur any health care costs, in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation